2019
DOI: 10.1038/s41598-019-54285-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between lipid profiles and presence of carotid plaque

Abstract: It is indicated that lipids profiles are associated with carotid plaque and Atherosclerosis. However, studies about the relationship between serum lipid profiles and carotid plaque composition in Chinese Population is limited. We conducted a cross-sectional study among 3,214 participants between January 2015 and December 2017 in China, to investigate the association between various lipid profiles and the prevalence of carotid plaque. Logistic regression model was used to investigate the association between pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
5
18
0
Order By: Relevance
“…The effect of cafferic acid on hepatocellular carcinoma may be related to the modulation of the gut microbiota and metabolites ( Zhang et al, 2017 ). FA itself has been identified to modulate the gut microbiota in previous studies ( Liu et al, 2019 ; Ma et al, 2019 ), which is consistent with our finding here. These studies suggest that FA could possibly influence the gut microbiota through its product, mainly cafferic acid.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The effect of cafferic acid on hepatocellular carcinoma may be related to the modulation of the gut microbiota and metabolites ( Zhang et al, 2017 ). FA itself has been identified to modulate the gut microbiota in previous studies ( Liu et al, 2019 ; Ma et al, 2019 ), which is consistent with our finding here. These studies suggest that FA could possibly influence the gut microbiota through its product, mainly cafferic acid.…”
Section: Discussionsupporting
confidence: 94%
“…Cardiovascular and cerebrovascular diseases, which mainly develop from atherosclerosis, have become the leading cause of death worldwide, especially in developed countries ( Liu et al, 2019 ). Atherosclerosis is characterized by excessive cholesterol deposition within the intima, especially in the aorta and coronary artery.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, high LDL-C was also found to be related to multiple CPs, which was in line with a previous study [19]. Consistent with other previous studies [28,29], low HDL-C was also associated with CP in the present study, which suggested that HDL-C may be a protective factor for carotid atherosclerosis. It is worth noting that in this study, high total cholesterol was not only associated with the presence of CP, but also with irregular CP.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have examined the association between lipid pro les and CP, but got inconsistent results [19,[27][28][29]. High LDL-C was found to be associated with the presence of CP [19,27,29], which was consistent with our ndings. However, an Algeria study failed to prove the association between high LDL-C and CP [28].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation